Intra-urban disparities in the quality of life in the city of Porto: a spatial analysis contribution - Luis Delfim Santos; Isabel Martins (European Regional Science Association (ERSA), 2014)
Geographical Information Systems (GIS) are an essential tool to integrate and manage large amounts of data (statistical and graphical) and to visualise the modelling efforts of the contemporary city. The further use of spatial analysis methods, in particular the exploratory analysis of data and spatial econometric models, is a promising way forward to analyse urban reality. In this analysis, we used a conceptual model and a geographical database developed for the city of Porto (Portugal) under a previous research on the topic of intra-urban disparities in the local quality of life. The aim of this paper is to contribute to the interdisciplinary debate on the relevance and use of this type of techniques, which enable us to describe spatial distributions, identifying patterns of spatial association, concentration areas or hot spots, in order to look into distributive features such as concentration, persistence and transitions that might provide interesting interpretations of complex territorial structures, such as the cities.
Keywords: R58; O21; 330; urban disparities; spatial analysis; quality of life